Concurrence of Bronchial Asthma, PCOS in Young Adolescent and its Management by Siddha Therapeutics - A Case Study (International Journal of Ayurveda and Pharma Research, 2023)
Growing evidence suggests that polycystic ovarian syndrome (PCOS) and Bronchial asthma coexist thanks to their common pathogenicity route. Both PCOS and Bronchial asthma has been associated with chronic low grade inflammation which results in hormonal disparity.  One such case of a young woman with a medical history of Bronchial asthma presented with complaints of irregular menstrual cycle with amenorrhea and episodes of asthmatic attack once a month. The laboratory investigations including both blood and sonographic studies revealed the elevated absolute eosinophilic count, serum IgE and bilateral polycystic ovarian cyst. The Patient has been treated with internal medications and was advised to continue the physical activity such as walk for once a day and Pranayama (breathing exercise) as an adjunct to the treatment. After the treatment period of about 10 months, the outcome was assessed by both clinical prognosis as well as with USG report. The case study is about managing PCOS as well as bronchial asthma by Siddha therapeutic intervention and efficacy of the chosen drugs towards the ailments has also been explained with the help of preclinical studies conducted on the individual herbs of the formulation included in the study. This study could help to explore the therapeutic potential of Siddha medicine towards alleviating the low grade inflammation and hormonal imbalances associated with both Bronchial asthma as well as PCOS.